Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/modpathol.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of histological cell type in high-grade endometrial carcinoma

Abstract: Subclassification of endometrial carcinoma according to histological type shows variable interobserver agreement. The aim of this study was to assess specifically the interobserver agreement of histological type in high-grade endometrial carcinomas, recorded by gynecological pathologists from five academic centers across Canada. In a secondary aim, the agreement of consensus diagnosis with immunohistochemical marker combinations was assessed including six routine (TP53, CDKN2A (p16), ER, PGR, Ki67, and VIM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
129
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 34 publications
1
129
0
2
Order By: Relevance
“…They are frequently expressed in low-grade to intermediate-grade EC (> 70% tumors) but are usually negative in CCC. 18,[47][48][49][50] However, they may be less useful in the setting of a high-grade EC, as up to two thirds of these tumors can exhibit a loss of expression of 1 or both receptors. 49 Hoang and colleagues examined the immunoexpression patterns of HNF1b and ER in endometrial CCC, EC, and serous carcinomas and observed moderate to strong, diffuse nuclear HNF1b staining and no ER expression in 14/15 CCCs and 1/15 serous carcinomas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They are frequently expressed in low-grade to intermediate-grade EC (> 70% tumors) but are usually negative in CCC. 18,[47][48][49][50] However, they may be less useful in the setting of a high-grade EC, as up to two thirds of these tumors can exhibit a loss of expression of 1 or both receptors. 49 Hoang and colleagues examined the immunoexpression patterns of HNF1b and ER in endometrial CCC, EC, and serous carcinomas and observed moderate to strong, diffuse nuclear HNF1b staining and no ER expression in 14/15 CCCs and 1/15 serous carcinomas.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the diagnosis of endometrial or ovarian carcinomas with a clear cell component is associated with low to moderate interobserver reproducibility. [16][17][18] The presence of focal or, less commonly, extensive areas of clear cells in endometrioid neoplasms may be 19 Squamous differentiation is not infrequently encountered in EC, and squamous cells can exhibit cytoplasmic clearing due to an accumulation of glycogen. However, EC with glycogenated squamous cells will almost invariably exhibit more typical foci of squamous metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inter-observer variability exists, even amongst expert gynecopathologists, when subtyping and grading endometrial. [1][2][3][4] In most cases, tumor cell type and grade are diagnosed based on hematoxylin and eosin slides according to the WHO histopathological criteria. 5 The use of immunomarkers for distinguishing subtype has increased during the past years.…”
mentioning
confidence: 99%
“…In some cases, distinguishing CCC from other carcinomas with ''clear cell features'' and benign clear cell mimics proves challenging, and multiple authors have reported low interobserver and intraobserver reproducibility of histologic cell type in highgrade ECs with and without the presence of clear cells. 16,17 To date, immunohistochemistry (IHC) has had modest use in improving diagnostic reproducibility of high-grade ECs. However, recent literature suggests that glypican 3, hepatocyte nuclear factor IA, and napsin A show promise in distinguishing CCC from other high-grade ECs.…”
mentioning
confidence: 99%